Bio-efficacy of sequential herbicide application for weed management in dry direct seeded rice - V K CHOUDHARY; ANIL DIXIT (The Indian Journal of Agricultural Sciences, 2021)
Weeds are the major biotic constraint in dry-direct seeded rice (DDSR), mainly due to the concurrent emergence and absence of water layer to suppress weeds. Therefore, strategy needs to be developed to get broad-spectrum weed control in DDSR. Experiments were conducted in rice (var. MTU 1010) during 2015-16 where sequential applications of pre- and post-emergence herbicides were evaluated for providing broad-spectrum weed management options in DDSR. Both the years, employing two-hand weedings at 15 and 30 DAS provided the lowest weed densities and weed dry weight at 75 DAS, whereas the maximum values of weeds were recorded in un-weeded plots. Among the herbicide-based weed management practices, application of pendimethalin 1000 g/ha fb bispyribac sodium 25 g/ha fb fenoxaprop 60 g/ha + chlorimuron + metsulfuron 4 g/ha at 30 DAS provided excellent weed control at 75 DAS, with 4.3% higher rice grain yield than two hand weedings at 15 and 30 DAS, pendimethalin 1000 g/ha fb bispyribac sodium 25 g/ha also provided good weed control and higher grain yield. Un-weeded plots noticed with considerable yield reduction of 79.5-83.3% over two hand weedings. Therefore, sequential application of pendimethalin 1000 g/ ha fb bispyribac sodium 25 g/ha is recommended along with need-based application of post-emergence herbicides (fenoxaprop 60 g/ha + chlorimuron + metsulfuron 4 g/ha) or one hand weeding to improve the weed control efficiency and provides economically higher productivity in DDSR.